Responses of immune organs after single-dose exposure to phenanthrene in yellowfin seabream (Acanthopagrus latus): CYP1A induction and oxidative stress - Shirmohammadi, Mehrnaz; Chupani, Latifeh; Salamat, Negin (Chemosphere, 2017)
The effect of phenanthrene (Phe) on induction of ethoxyresorufinO-deethylase (EROD) activity and oxidative stress was examined in immune organs of yellowfin seabream Acanthopagrus latus. Fish were treated with a single intraperitoneal injection at 2, 20, or 40 mg kg-1. The Phe concentration in spleen, EROD activity, superoxide dismutase (SOD) and catalase (CAT) activity, ascorbic acid (AsA), total glutathione (GSH), lipid peroxidation (LPO), and protein carbonylation (PC) levels in spleen and head kidney were assessed at one, four, seven, and 14 days post-injection. Dose response relationship was explored for data on day four. Phe concentration reached the highest observed level on day four, showed decline on day seven, and was undetectable at the end of trial. EROD activity in both organs followed the pattern of Phe level in all treated groups. Catalase and SOD activity at low Phe concentrations was significantly higher than controls, while LPO and PC level showed no differences from controls. In contrast, at 20 and 40 mg kg-1, CAT and SOD activity, an indicator of oxidative stress, was significantly lower than in untreated controls, while AsA, GSH, LPO, and PC levels were higher on days 4 and 7. No parameter of any treatment group in either organ tissue showed difference from control values at the end of the experiment. The SOD and CAT activity in both organs exhibited a biphasic (initial stimulatory effect) effect, whereas other parameters showed a monophasic effect in terms of dose-response. Results suggest that Phe induced CYP1A and antioxidant responses in immune organs.
Keywords: EROD activity; Animals; Kidney; Phenanthrenes; katalasa; Superoxide Dismutase; Sea Bream; Antioxidants; glutathion; oxidační stres; chemické látky znečišťující vodu; Catalase; Glutathione; superoxiddismutasa; Water Pollutants, Chemical; Protein Carbonylation; Oxidative Stress; glutathiontransferasa; Glutathione Transferase; Cytochrome P-450 CYP1A1; Detoxification; peroxidace lipidů; Polycyclic aromatic hydrocarbons; oxidace-redukce; Lipid Peroxidation; mořan zlatý; Oxidation-Reduction; karbonylace proteinů; fenantreny; antioxidancia; cytochrom P-450 CYP1A1; Oxidative damage; Immune organs; zvířata; ledviny